SUSTAINABLE URBAN TRANSFORMATION RETHINKING BUILT ENVIRONMENT DEVELOPMENT THROUGH ADAPTIVE REUSE TECHNIQUES AND TECHNOLOGY - Bothma, Cobus (University of Pretoria, 2022)
Dissertation (MArch.Prof)--University of Pretoria, 2021